DIGITALIZATION OF THE ECONOMY: PROBLEMS AND PERSPECTIVES OF THE RUSSIAN FEDERATION - V. Akinina; A. Khakirov (Вестник Северо-Кавказского федерального университета)
Our society is a constantly developing system that is undergoing metamorphosis every scientific and technological revolution. The fourth scientific and technological revolution led to the emergence of completely new technologies that minimize human participation in the production process through its automation and computerization. In recent years, the Russian Federation has experienced many difficulties both on the world stage and within the country, which did not allow it to start the process of digitalization. This factor characterizes Russia's lagging behind other countries in creating a digital economy. The study presents the main problems faced by the Russian economy and society on the path of digital transformation.